2012
DOI: 10.5846/stxb201105020571
|View full text |Cite
|
Sign up to set email alerts
|

Longitude gradient changes on plant community and soil stoichiometry characteristics of grassland in Hulunbeir

Abstract: In large scale, plant stoichiometry is mainly affected by latitude and longitude. Many works has have been done to study the effects of temperature on plant stoichiometry along the latitude gradient, while researches on the precipitation along the longitude gradient are rare. In this research, we studied the stoichiometry characteristics of grassland communities along the longitude gradient in Hulunbeir. The results showed as follow: 1) the range of leaf carbon was 440. 76-452. 72 mg / g, leaf nitrogen was 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
0
1
Order By: Relevance
“…In addition, we observed that leaf N and P concentrations decreased with increasing LAT and LON for meadow halophytes. This finding was not in line with the overall results of the study whereas appeared to be consistent with the field observations of plant community in the HunLunbeier Grassland ( Ding et al., 2012 ). Consequently, the overall patterns of leaf N and P stoichiometry patterns in halophytes were strongly controlled by large-scale geographical factors but simultaneously exhibited variations among diverse geographical locations.…”
Section: Discussioncontrasting
confidence: 67%
“…In addition, we observed that leaf N and P concentrations decreased with increasing LAT and LON for meadow halophytes. This finding was not in line with the overall results of the study whereas appeared to be consistent with the field observations of plant community in the HunLunbeier Grassland ( Ding et al., 2012 ). Consequently, the overall patterns of leaf N and P stoichiometry patterns in halophytes were strongly controlled by large-scale geographical factors but simultaneously exhibited variations among diverse geographical locations.…”
Section: Discussioncontrasting
confidence: 67%
“…Since then, ecological stoichiometry has rapidly developed in recent years in China. Research has focused on forest [14][15][16], grassland [17][18][19] and wetland ecosystems [20][21][22] and the effect of fertilizers on N:P ratios [23,24]. In general, the research has been broad, showing a trend of taking forest, the largest ecosystem on land, as the dominant ecosystem.…”
Section: Introductionmentioning
confidence: 99%